PENINGKATAN KETERAMPILAN BOGA DASAR MELALUI METODA DEMONSTRASI - Erdiana Erdiana (JS (JURNAL SEKOLAH), 2019)
Abstract: Enhancing Basic Catering Skills Through Demonstration Methods. In contextual classrooms, the teacher's job is to help students achieve their goals. For this reason, an appropriate strategy is needed to improve the results and quality of learning, especially basic culinary subjects in the skill expertise of SMK 3 in Pekanbaru. The application of the demonstration method will make a major contribution, especially in improving basic food skills. From the observations of the first cycle obtained 50% of students completeness, while the second cycle 97.06% students completeness. Here an increase of 47.06% mastery of students. The use of the demonstration method is not only until the second cycle, but can be used continuously to obtain maximum results.Keywords: skills, basic food, demonstration methodAbstrak: Peningkatan Keterampilan Boga Dasar Melalui Metoda Demonstrasi. Dalam kelas kontekstual, tugas guru adalah membantu siswa mencapai tujuannya. Untuk itu diperlukan strategi yang tepat dalam peningkatan hasil dan kualitas dari pembelajaran, khususnya mata pelajaran boga dasar pada kompetensi keahlian Tata Boga SMK Negeri 3 Pekanbaru. Dengan penerapan metode demonstrasi akan memberikan kontribusi yang besar terutama pada peningkatan keterampilan boga dasar. Dari hasil observasi siklus I diperoleh 50 % ketuntasan siswa, sedangkan siklus II 97.06% ketuntasan siswa. Disini terjadi peningkatan sebesar 47.06 % ketuntasan siswa. Penggunaan metode demontrasi tidak hanya sampai siklus II saja, tetapi bisa digunakan secara kontiniu untuk memperoleh hasil yang maksimal.Kata Kunci: keterampilan, boga dasar , metode demonstrasi